Diagnostic outcomes of CT-guided lung biopsy in an HIV and TB co-infection prevalent region - van Rensburg, Juan Janse (Division of Radiology, 2025)
Background: Tuberculosis (TB) and the Human Immunodeficiency Virus (HIV) are a major burden on the health of the people in the Western Cape with approximately 56 000 new cases of TB diagnosed in 2018 and 16 287 incident cases of HIV during the same period. CT-guided lung biopsy is a limited resource primarily used for diagnosing suspected cancer. TB is occasionally diagnosed on samples obtained by CT-guided lung biopsy. Objectives: To quantify the burden of TB on the CT-guided lung biopsy (CTLB) service at Groote Schuur Hospital (GSH). Secondary aims include summarising the diagnoses observed in an HIV-positive subset and comparison of diagnostic performance of different methods for TB diagnosis on biopsy samples. Method: A retrospective review of results from 406 consecutive CTLB performed at a tertiary hospital in the Western Cape during 2018 and 2019. Results: The mean age of subjects was 61 years, and the male to female ratio 1.1:1. A total of 40 specimens (9.9%) had confirmed tuberculosis, 264 (65%) had malignancy, and 3 had concurrent TB and malignancy. Conclusion: This study confirmed a high yield of TB among CTLB specimens as expected in a TB-prevalent region. There was also a higher proportion of TB and of non-TB non-malignant causes of lung nodules and masses in the HIV-positive subset as compared to HIV negative subjects.